Pengaruh Konsep Penjualan Syariah Terhadap Minat Beli Konsumen di Toko Emas Sejati Baru Plaza Kebun Sayur Balikpapan Menurut Perspektif Ekonomi Syariah - Syauqi, Ahmad; Iskandar Yusuf (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The application of the sharia sales concept also influences consumer buying interest through the mechanism of fair pricing. The purpose of this study is to determine the effect of the sharia sales concept on consumer buying interest at Sejati Baru Jewelry Store in Plaza Kebun Sayur Balikpapan from an Islamic economic perspective. The method used in this study is descriptive quantitative. The results of this study indicate that the sharia sales variable significantly contributes to variations in consumer buying interest, with an R square value of 0.285, indicating that 28.5% of the variation in buying interest can be explained by this variable. Additionally, the F test and t test also show strong significance, with p-values well below 0.05.